The tragedy of German Jesuits working in Chinhoyi Diocese during Zimbabwe s war of Liberation - Chakawa, Joshua (Midlands State University, 2014)
The Catholic Church emerged out of the liberation war in 1980 as battered, numbed and depleted by the deportation of several of its rural clergy and the murders of its misionaries, nuns and lay people working in parishes which were located in the main theatres of the war. The Catholic church was accused by the Rhodesian government of being riddled with communism yet at the same time missionaries were brutalized by armed guerrilla assailants. The paper studies the experiences of some of the missions in the then Sinioa Prefecture (now Chinhoyi Diocese). The missions under study are St. Albert s, Kangaire, St Rupert s, St Boniface and St Paul s. It begins with the history of Jesuits in Zimbabwe, the establishment of the missions and then goes on to explain circumstances surrounding the misfortune of these missions. The escalation of the war saw St Ruperts, Kangaire and St Albert s closing between 1978 and 1979. At St Ruperts, the two German missionaries present were killed and a German priest was murdered at Kangaire. St Boniface mission lost its African catechist and closed as well.